The use of intranasal glucocorticosteroids in patients with chronic rhinosinusitis in the preoperative period - I. I. Chernushevich; A. N. Naumenko; A. V. Voronov; A. Y. Golubev; E. E. Kozyreva (Медицинский совет, 2022)
Introduction. Chronic rhinosinusitis is a disease that occurs everywhere, characterized by inflammation of the mucous membrane of the paranasal sinuses and nasal cavity. If it is impossible to eliminate the causes of the recurrent disease with medical therapy, the use of surgical treatment help to recover the normal functioning of the ostium, including the ostiomeatal complex to improve ventilation and drainage of the paranasal sinuses and recover nasal breathing to relieve chronic inflammation.Purpose of the study. Assessment of the degree of intraoperative bleeding in patients with chronic rhinosinusitis.Materials and methods. On the basis of the FGBU SPB Research Institute of ENT of the Ministry of Health of the Russian Federation in the period from 2020 to 2021. the study of the effect of local intranasal glucocorticosteroids (INGKS) in the intraoperative period in patients with chronic polypous rhinosinusitis was carried out. The total amount of blood loss during surgery for chronic polypous rhinosinusitis in patients who used mometasone furoate preoperatively and in patients not taking topical hormonal drugs was analyzed.Results. In the study group, the average blood loss per operation was 257 ml, in the control group – 401 ml. In patients who took intranasal glucocorticosteroids during surgery, the intensity of bleeding is less pronounced. Undoubtedly, there are many reasons that affect the intensity of bleeding in general, however, a decrease in the inflammatory response in the nasal cavity and a decrease in inflammatory metabolites have a beneficial effect on the state of the nasal mucosa.Conclusion. The use of intranasal glucocorticosteroids in the preoperative period has a positive effect on reducing the inflammatory process in the nasal cavity, which helps to reduce the intensity of intraoperative bleeding.